PELATIHAN MEMBUAT KELAS DAN SOAL MATEMATIKA DI GOOGLE CLASS ROOM DI MTs SWASTA YPI SUBULULHUDA DESA SAENTIS - Rusmini; Doni Irawan Saragih (Universitas Majalengka, 2021)
Education and training is one of the fundamental things in human life, this training aims to provide information on how to create classes and create questions on the Google form in the Google Classroom application. This activity was carried out for 1 day face to face by following the health protocol where the activity was only attended by 10 people. This training was conducted at YPI Subululhuda, Saentis Village. After the training and mentoring show that the participants had a better motivation and level of knowledge than before, the activity regarding making classes and math problems on the Google form in the Google classroom application. For the continuation program by evaluating the activities of teachers at YPI Subululhuda Saentis Village online using Zoom or Whats app media.